The Abstract Book of the XXIII Conference of Junior Researchers in Psychology - Grigaitė, Agnė; Vilutytė, Lauryna; Tilingaitė, Jurgita (Vilnius University Proceedings, 2026)
Conference of Junior Researchers in Psychology is an annual event organised by the doctoral students of the Institute of Psychology of Vilnius University. The conference provides an opportunity for psychology students and young researchers from Lithuanian and foreign universities to present their research and discoveries. This year's conference was dedicated to exploring psychology today as a field existing between stability and change, highlighting both enduring foundations and emerging transformations.Jaunųjų mokslininkų psichologų konferencija – kasmetinis Vilniaus universiteto Psichologijos instituto doktorantų organizuojamas renginys. Konferencija suteikia galimybę Lietuvos ir užsienio universitetų psichologijos studentams ir jauniesiems mokslininkams pristatyti savo mokslinius tyrimus ir atradimus. Šių metų konferencija buvo skirta nagrinėti šiuolaikinę psichologiją kaip discipliną, veikiančią tarp stabilumo ir kaitos, atskleidžiant tiek išliekančius pagrindus, tiek vykstančius pokyčius.
Keywords: unior researchers; abstract book; psychology conference